CLINICAL CHARACTERISTICS OF PATIENTS WITH TRICHOPHYTHIA (World Bulletin of Public Health, 2023)
Trichophytosis is a widespread disease from the group of dermatomycosis. However, the incidence rate in different regions of the world is different, which is associated with natural and geographical features, social and economic priorities, the traditional way of life and insufficient sanitary and epidemiological population. Changes in ecology, urbanization and associated changes in the boundaries of nosoareals lead to changes in the epidemiology and nature of the clinical course of dermatomycosis. The incidence of dermatophytosis fluctuates in different time periods and qualitative main stages in the development of public health, with the use of sanitary and preventive work, perspectives.